Elevated Plasma and Liver tissue Uric Acid Levels in Alloxan Diabetic Rats (Bangladesh Journal of Medical Science, 2021)
Background: Abnormal levels of serum uric acid (UA) causes major health problem due to itspivotal role in the etiology of many systemic diseases. Many research works in recent past haveshown elevated uric acid levels in diabetic subjects. Some reports indicate that uric acid elevationis related to diabetic complications, whereas a few claimed that uric acid elevation is also seen inpre-diabetic condition.The reason for this elevation of uric acid and a possible role of insulin inthis regard is obscure. Hence a study has been undertaken to assess the uric acid status in alloxandiabetic rats with an attempt to establish the possible cause for uric acid elevation.Methods:The studies were carried out on healthy male Wistar rats with a body weight of 150-180g. Therats were divided into two groups,normal group (Group-1) and alloxan diabetic group (Group-2)with six animals in each group. Induction of diabetes was done by administering a singleintraperitoneal injection of freshly prepared aqueous solution of Alloxan Monohydrate (150mg/Kg body weight) prepared in normal saline, to the overnight fasted rats. After the stipulatedperiod of 30 days, the animals (Group-1 and Group-2) were anesthetized using Isoflurane andsacrificed. They were dissected immediately and liver tissue was procured, blotted to removeblood stains, and placed in cold phosphate buffer saline (pH7.4). Blood samples were collectedusing heparin as anticoagulant.The uric acid levels in plasma, erythrocytes and in liver tissueas well as the levels of ADA in plasma and liver tissue were estimated.Results: A significant(p